The Roles of Fractionated Potentials in Non-Macroreentrant Atrial Tachycardias Following Atrial Fibrillation Ablation: Recognition Beyond Three-Dimensional Mapping - Wang, Yu-Chuan; Shi, Li-Bin; Chu, Song-Yun; Solheim, Eivind; Schuster, Peter; Chen, Jian (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Non-macroreentrant atrial tachycardia (nAT) following atrial fibrillation (AF) ablation is being increasingly reported. Many issues remain to be elucidated. We aimed to characterize the fractionated potentials (FP) in nAT and introduce a new method of cross-mapping for clarifying their roles. Methods and Results: Forty-four nATs in 37 patients were included and classified into focal AT (FAT, 12), microreentrant AT (MAT, 14), and small-loop-reentrant AT (SAT, 18) groups, according to activation pattern. FP was found on all targets except nine FATs. The ratio of FP duration to AT cycle length (TCL) was different among groups (28±7% in FAT, 53±11% in MAT and 42±14% in SAT, p<0.05) and ablation duration were longer in SATs (313±298 vs, 111±125 s, p<0.05). The ratio of mappable CL to TCL was shorter in the FAT group (63±22% vs. 90±9% and 89±8%, p<0.05). When cross-mapping was employed, trans-potential time differences in both longitudinal and transverse direction were longer around the culprit FP for MAT (p<0.01). After Receiver Operating Characteristic curve analysis, it is best to adopt the sum of time difference ratios in both directions ≥60% as a cut-off value for discrimination of the FPs responsible for MAT with a sensitivity of 92% and specificity of 87%. Conclusions: FP can be found on target in most nATs following a previous AF ablation. The ratio of FP duration to TCL may help for differentiation. A simple and effective method of cross-mapping could be employed to clarify the roles of FPs.